Geochemical Characteristics of Apatite in Heavy REE‐rich Deep‐Sea Mud from Minami‐Torishima Area, Southeastern Japan. Issue 1 (January 2014) - Kon, Yoshiaki; Hoshino, Mihoko; Sanematsu, Kenzo; Morita, Sayaka; Tsunematsu, Maiko; Okamoto, Nobuyuki; Yano, Nobuhiko; Tanaka, Mikiya; Takagi, Tetsuichi
Abstract: We have conducted geochemical and mineralogical investigations of the rare earth and yttrium (REY)‐rich mud from the Minami‐Torishima area in the Pacific in order to clarify the concentration of REY and their host‐phase in the mud. X‐ray diffraction analysis shows that the mud is mainly composed of phillipsite, fluorapatite, quartz, albite, illite and montmorillonite. Whole‐rock CaO, P2 O5 and total REY contents of the mud are positively correlated. Relative abundance of apatite is also positively correlated to P2 O5 and total REY contents. These correlations suggest that apatite is the main host of the P2 O5 and REY in the mud. We make in situ compositional analyses of constituent minerals in the REY mud. The results show that the apatite is abundant in REY (9300–32, 000 ppm) and is characterized by a negative Ce anomaly and enrichment in heavy rare‐earth elements. This abundance and composition of REY of the mud is similar those of fish debris apatites. In contrast, phillipsite is less abundant in REY (60–170 ppm). Therefore we conclude that the main REY host phase of the mud is apatite. Abstract : We have conducted geochemical and mineralogical investigations of the rare earth and yttrium (REY)‐rich mud from Minami‐Torishima area in the Pacific in order to clarify the concentration of REY and their host‐phase in the mud. In‐situ compositional analyses of constituent minerals in the REY‐mud show that the apatite is abundant in REY (9300–32000 ppm) and phillipsite is less abundant in REY (60–170 ppm). Therefore we conclude that the main REY host phase of the mud is apatite.